Polycaprolactone Mesh for Asian Rhinoplasty: Outcomes and Complications of Composite Septal Extension Graft Compared to Mesh-Only Graft - Hyun, Seung; Cho, Seung Woo; Baek, Rong-Min (Facial Plastic Surgery, 2021)
Despite the great demand of aesthetic rhinoplasty in Asian population, it is difficult to obtain the lasting ideal tip projection along with lengthening of the nose due to the small and weak nasal septum. The shortage of available septal cartilage to work with is another major obstacle. A retrospective study was conducted between January 2017 and December 2019 in Seoul, Korea. A total of 774 patients underwent septorhinoplasty using polycaprolactone (PCL) mesh for the cosmetic enhancement of the nasal tip and the projection. Comparisons of aesthetic outcomes, patients' satisfaction surveys, and complications were performed between PCL mesh-only group and composite PCL group. Of all the patients, 97.5% of the patients in composite PCL group were rated more than 3 scores in aesthetic outcomes, whereas 90.4% in mesh-only group (p-value = 0.0002). About 96.7% of the patients with composite PCL rated their satisfaction level as more than satisfied, whereas 94.3% in mesh-only group (p-value = 0.0365). Overall, there were 17 patients in composite PCL group who exhibited complications including decreased tip projection, deviated nasal tip, mesh infection, and mesh exposure. However, there were two patients who had mesh injection in mesh-only group. Septorhinoplasty with septal extension graft using composite PCL graft provides robust support to the aesthetically modified projection and the lengthened nose without obvious complications on the nasal tip. Such technique allows surgeons to overcome the nature of Asian nose that is weak and small, and also provides satisfaction to patients who desire ideal tip projections and dramatic changes.
Keywords: polycaprolactone; PCL mesh; composite septal extension graft; nasal tip